La faillite de l’entreprise d’Etat en droit polonais (Contemporary Central & East European Law, 1986)
The article tackles the problem of the state-owned enterprises’ insolvency accordingly to the Law of the 25th September 1981 on the state-owned Enterprise. As their functioning, except public utility enterprises, is based on the self-financing, they can be subject to liquidation or insolvency. The insolvency is regulated by the Law of the 29th June 1983 on the improvement of the economic situation of the state-owned  enterprise and its insolvency and the Regulation of the President of the Republic of Poland from 24 October 1934 which are analysed in the further part of the article. It is highlighted that the possibility of insolvency of the state-owned enterprise was introduced by the regulation from 1981 and was not provided, neither in the Decree of 3rd January 1987 on the creation of state-owned enterprises, nor in the Decree of 26th of October 1950 on the state-owned enterprises.There are three groups of enterprises excluded from this legal act. The first group concerns Polish Railways, Polish Airlines LOT and state’s banks. In the second group, we can find those enterprises which can declare the insolvency only voluntarily (enterprises working under the supervision of the Ministry of Finances or Ministry of Defence or for this Ministries, and certain enterprises under supervision of Ministry of Justice). The third group concerns the public utility enterprises.Next part of the article analyses the procedure of insolvency. Primary aim is to guarantee, at least partial, satisfaction of creditors’ claims. Secondly, it lets the responsible person to limit personal liability to the value of the moral person’s assets. Thirdly, it should simulate the economic activity and the effectiveness of the enterprises by eliminating those operating for loses and by passing their assets to the enterprise which would make a better usage of it.The further part of the article lists the subjects who can initiate the procedure of insolvency. These are: the director responsible for the enterprise, the liquidator, the resolution committee, the founding organ and the bank which finances the enterprise in question. The reasons for which each of the aforementioned subjects can demand the insolvency are analysed in detail thereafter.The adopted law mentions two conditions under which the procedure of insolvency can be initiated. The first is the impossibility, confirmed in the balance sheet, to cover the enterprise’s obligations by its assets. The second is lack of regulation of debts for six months after the creditor’s formal demand. These two conditions are independent from each other and do not have to be meet together.The administration of the enterprise  is entrusted to the trustee, who can be physical or legal person, designed by the Council of Ministers. The labour contracts with employees are terminated with upon prescript notice period.  Under certain conditions, it is possible to initiate a corrective programme which may help to avoid the insolvency, what is analysed in details in the last part of the article.